2012
DOI: 10.4028/www.scientific.net/kem.504-506.845
|View full text |Cite
|
Sign up to set email alerts
|

Viscoplastic Regularization of Local Damage Models: A Latent Solution

Abstract: Abstract. Local damage models are known to produce pathological mesh dependence in finite element simulations. The solution is to either use a regularization technique or to adopt a non-local damage model. Viscoplasticity is one technique which can regularize the mesh dependence of local damage model by incorporating a physical phenomenon in the constitutive model i.e. rate effects. A detailed numerical study of viscoplastic regularization is carried out in this work. Two case studies were considered i.e. a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The failure predictions were improved significantly and the strain localization length scale were obtained very accurately. Mesh independent damage distribution was obtained for the cross die drawing test without introducing any arbitrary regularization parameter [21]. It is worth mentioning that dual phase steel has a rate dependent hardening characteristics and the cross die drawing is carried out a punch velocity of 1 mm/s, which is normal punch speed in deep drawing process.…”
Section: Discussionmentioning
confidence: 99%
“…The failure predictions were improved significantly and the strain localization length scale were obtained very accurately. Mesh independent damage distribution was obtained for the cross die drawing test without introducing any arbitrary regularization parameter [21]. It is worth mentioning that dual phase steel has a rate dependent hardening characteristics and the cross die drawing is carried out a punch velocity of 1 mm/s, which is normal punch speed in deep drawing process.…”
Section: Discussionmentioning
confidence: 99%
“…Local continuum damage models are known to cause pathological mesh dependence in finite element simulations due to strain softening. 27 Various approaches were proposed to address mesh dependence. Rabczuk and Belytschko 28,29 proposed a novel approach for modeling discrete cracks in meshfree particle methods by using a local enrichment of the test and trial functions with a sign function to deal with the discontinuities at particles around the crack surface.…”
Section: Constitutive Model Formulationmentioning
confidence: 99%
“…Viscoplastic regularization was employed as an alternative approach by Niazi et al to address the issue of pathological mesh dependence. 27 One method for regularizing the mesh dependency of the local damage model is viscoplasticity, which involves introducing rate effects-a physical phenomenon-into the constitutive model. This technique was successfully used by Niazi et al with a local anisotropic damage model to predict failure in a cross die drawing process with the actual physical process parameters.…”
Section: Constitutive Model Formulationmentioning
confidence: 99%
“…Several works, such as by Needleman , Sluys and De Borst , and Niazi et al . , showed that by including rate effects, the mesh dependence could be reduced significantly. A disadvantage is that this technique can only be applied to transient loading conditions .…”
Section: Materials Modelingmentioning
confidence: 99%